Managing raw materials of vegetable origin increases fungal indoor concentration in food companies - Elizondo Zertuche, Mariana; Martínez Carranza, Karen; Orue, Nydia; de Jesús Treviño Rangel, Rogelio; Robledo Leal, Efrén Ricardo (Association of Food Scientists & Technologists, 2020)
Fungi in indoor environments is a known cause of disease and food spoilage. However, there is currently no legislation or normativity stablishing limits for fungal densities in correlation with these. Moreover, there is little knowledge of the diversity of fungi in indoor environments for industrial areas and in food-related companies in particular, a study has never been performed to evaluate the concentration and diversity of fungi in this type of places. We evaluated the fungal density of 20 food companies. We sampled 100 L of air onto rose bengal-malt extract-agar plates, using an Air Test Omega sampler. After incubation, CFUs were counted and identified. Penicillium, Cladosporium and Aspergillus were the most commonly isolated genus, with Penicillium being the only genus to be present in every area sampled. Neither the companies’ location nor their room temperature influenced the fungal densities significantly, however, companies using vegetable raw materials had a significantly greater concentration of fungi than the rest of the companies. While all concentrations were within previously suggested levels from a health-related point of view, more information is needed that correlates fungal concentration with food spoilage in order to suggest a range of concentrations focused for food companies’ product preservation.